2014
DOI: 10.1182/blood.v124.21.182.182
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Published Single-Nucleotide Polymorphisms (SNPs) Associated with Cytomegalovirus Infection and Disease after Hematopoietic Cell Transplantation in a Large Caucasian Cohort

Abstract: Background: Cytomegalovirus (CMV) infection is one of the most common complications after hematopoietic cell transplantation (HCT). Regardless of preemptive therapy for CMV infection, CMV disease still occurs in approximately 10% of seropositive HCT recipients, resulting in high mortality. A number of studies have reported the association between CMV infection or disease and single-nucleotide polymorphisms (SNPs), however the results have not been validated in independent cohorts. We performed a candidate gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Host-specific differences in the TLR9 gene are likely to alter the course of an adaptive immune response, especially in a chronic infection like HIV or CMV. To date, the TLR9 SNPs have been showing to modulate the risk of CMV infection in individuals with the allogeneic hematopoietic stem cell transplantation (allo-HSCT) [ 11 , 12 ], renal transplant recipients [ 13 , 14 ], and infants [ 10 , 15 ]. The TLR9 2848C/T SNP was associated with congenital CMV infection in fetuses and infants [ 10 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Host-specific differences in the TLR9 gene are likely to alter the course of an adaptive immune response, especially in a chronic infection like HIV or CMV. To date, the TLR9 SNPs have been showing to modulate the risk of CMV infection in individuals with the allogeneic hematopoietic stem cell transplantation (allo-HSCT) [ 11 , 12 ], renal transplant recipients [ 13 , 14 ], and infants [ 10 , 15 ]. The TLR9 2848C/T SNP was associated with congenital CMV infection in fetuses and infants [ 10 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A significant correlation between the 1635 GG genotype and low average CD4 + T cell count during the viremic period in HIV-infected patients was found in the second study [ 27 ]. The donor genotype at the rs352140 SNP was significant for CMV disease in recipients following HSCT [ 11 ]. Clinical evidence has also demonstrated that the donor homozygous recessive genotype of the TLR9 1635A/G SNP was associated with a higher incidence of CMV reactivation and yielded a protective effect against acute graft versus host disease in allo-HSCT recipients [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations